Analysis and distribution of the rainfall monitoring network in a Brazilian Pantanal Region. - CRISTALDO, M. F. (2017)
ABSTRACT: To better understand drought and flood dynamics in the Pantanal is crucial an adequate hydrometeorological monitoring network. However, few studies have investigated whether the current monitoring systems are suitable in this region. Here, we analyzed the hydrometeorological monitoring network of the Aquidauana region, composed of pluviometric, meteorological and fluviatile gauging stations. We obtained data of all hydrometeorological gauges available in this region to compare with the World Meteorological Organization (WMO) recommendation. We found that although the number of stations in operation is satisfactory when compared with that established by the WMO, the network is not satisfactory in the operating stations because of lack of maintenance, thus creating a need for additional stations. This fact was also observed when analyzing the meteorological network. Using remote sensing data may be possible to fill these data gap. However, to improve the knowledge on hydrological processes in this region is still necessary to install additional ground-based stations. RESUMO: Para entender melhor a dinâmica de seca e inundação no Pantanal é fundamental uma rede de monitoramento hidrometeorológico adequada. No entanto, poucos estudos têm investigado se os atuais sistemas de monitoramento são adequados nesta região. Aqui, analisamos a rede de monitoramento hidrometeorológico da região de Aquidauana, composta por estações pluviométricas, meteorológicas e fluviais. Obtivemos dados de todos os medidores hidrometeorológicos disponíveis nesta região para comparação conforme a recomendação da Organização Meteorológica Mundial (OMM). Constatou-se que, embora o número de estações em operação seja satisfatório quando comparado com o estabelecido pela OMM, a densidade da rede não é satisfatória nas estações de operação por falta de manutenção, criando assim a necessidade de estações adicionais. Esse fato também foi observado na análise da rede meteorológica. O uso de dados de sensoriamento remoto pode ser possível para preencher essa lacuna de dados. No entanto, para melhorar o conhecimento sobre os processos hidrológicos nesta região ainda é necessário instalar estações terrestres adicionais.